White River crossing : a novel - McGuire, Ian (Crown, 2026)
"A ragged fur peddler arrives at a remote outpost of the Hudson Bay Company in the winter of 1766 with a lump of gold, claiming that there is plenty more like it further north at a place called Ox Lake. The outpost's chief factor, Magnus Norton, dreams of instant riches and launches a secret and perilous expedition to find the treasure and bring it back. Led by a family of native guides, the party of prospectors includes Norton's brutish deputy, John Shaw, and Thomas Hearn, the insular and intellectual first mate from the factory's whaling sloop. During their long journey north, Shaw's callousness and arrogance lead him to commit an act of sexual violence whose disastrous consequences will only fully emerge once they reach their final destination. There, amidst the bleak beauty of the Barren Grounds, as Norton's carefully crafted plans begin to fall apart and the brutal arctic winter starts to descend, Hearn is forced to make a choice that will define his character and determine his future forever. Utterly captivating, White River Crossing transports us back to the furthest edges of the eighteenth-century British empire where two radically different worlds-indigenous and European-collide with calamitous and deadly results"--